The influence of sex education video on parents’ sex education behaviors - Eko Suryani; Margono Margono (Poltekkes Kemenkes Yogyakarta, 2018)
In 2014, there were 455 cases which related to the violence against children. This kind of cases mostly happened in Yogyakarta and Sleman. The chief of Yogyakarta Agency of Woman and Community Empowerment (BPPM) DIY said that the majority victims of sexual violence were girls and there were 245 cases recorded. To avoid violence and discrimination against children, it requires the involvement of all components in society. One of the efforts is to encourage families to have knowledge and skills in parenting as a preliminary step to avoid it. It is because family is the foundation for character building, moral value, and education to children. This research aims to know the relationship between sex education video and parent’s behavior of sex education at Nogosaren Elementary School. The current research used quasi-experiment pre- and post-test design with control and experimental groups. The samples of this research were 102 respondents. The average score of parent’s behavior before watching sex education video was 66,76. Meanwhile, the respondents who had watched the sex education video had an average score of 77,59. According to data analysis using a paired t-test, it was known that there was a statistically significant gap with t-test p = 0.000 (p<0.05). The results of the research indicated that sex education video influenced parent’s sex education behaviors at SD N Nogosaren.